A solution for sea-sand reinforced concrete beams. (20th April 2019) - Su, Mei-ni; Wei, Liang-liang; Zeng, Zhi-wen; Ueda, Tamon; Xing, Feng; Zhu, Ji-Hua
Highlights: This study uses both ICCP and SS techniques to strengthen sea-sand RC beams. An experimental program consisting of 11 beams subjected to accelerated corrosion and ICCP was carried out. The ICCP-SS retrofitting method is effective in retarding the corrosion and recovering the capacity of RC beams. This proposed repairing method is beneficial for the durability of RC structures in coastal areas. The existing design methods are found to be rather conservative for the flexural design of retrofitted beams. Abstract: The popularity of reinforced concrete (RC) structures leads to increasing demand for sands, cement, aggregates and other raw materials. In the recent decades, river sand has been used to replace sea-in order to solve the resource shortages in many countries. However, sea-sand concrete might cause corrosion of steel re-bars and result in structure deterioration. Impressed current cathodic protection (ICCP) is an efficient method to prevent corrosion of re-bars, while bonding carbon fibre mesh to the RC structures can help improve the loading capacity of the deteriorated structures. This study proposes a new dual-functional intervention method, the impressed current cathodic protection – structural strengthening (ICCP-SS) method, to retrofit the deteriorated sea-sand RC structures by using the carbon – fabric reinforced cementitious matrix (C-FRCM). The C-FRCM composite, comprised of carbon fabric mesh and inorganic cementitious matrix, is both the anodic material for ICCP and the structural strengthening material. This paper presents an experimental program consisting of 11 simply supported beams, 9 of which were casted by simulated sea-sand and subjected to accelerated corrosion for 130 days. The specimens casted with simulated sea-sand were afterwards externally bonded with C-FRCM composite, exposed to ICCP for another 130 days, and finally tested. In this study, the loading capacity and deflection at midspan of the beams, as well as the open circuit potential (OCP) of re-bars were measured to assess the effectiveness of the intervention method. The proposed method has been shown to be effective in retarding the corrosion of steel re-bars and improving the loading capacity of the corroded specimens. In addition, this paper compares the experimental results with the capacity predictions set out in ACI 440.2R-08 for FRP strengthening system and ACI 549.4R-13 for FRCM strengthening system, which have been found to be rather conservative for the flexural design of retrofitted beams.